2007
DOI: 10.1007/bf03019923
|View full text |Cite
|
Sign up to set email alerts
|

Epidural ketamine for postoperative analgesia in the elderly

Abstract: BACKGROUND: In this pilot study we examined the use of epidural ketamine as an opioid alternative for postoperative analgesia in elderly patients undergoing major abdominal surgery. METHODS: With the approval of the local REB we approached patients older than 65 years scheduled for major abdominal surgery. After obtaining written informed consent 20 patients were allocated to receive a bolus of epidural bupivacaine 0.125% supplemented either with epidural ketamine 40mg (ketamine group) or epidural morphine 2mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…A strong case can be made for the intrinsic toxicity of ketamine, however [32]. To my mind, it is clear that ketamine should not be administered spinally, especially in view of the fact that the gains are not impressive [37]. In the vein of neurological toxicity, permanent anosmia has also been reported in a patient on long-term (6 months) therapy with intranasal ketamine for chronic pain [38], a route that has been questioned previously [39].…”
Section: Toxicitymentioning
confidence: 95%
“…A strong case can be made for the intrinsic toxicity of ketamine, however [32]. To my mind, it is clear that ketamine should not be administered spinally, especially in view of the fact that the gains are not impressive [37]. In the vein of neurological toxicity, permanent anosmia has also been reported in a patient on long-term (6 months) therapy with intranasal ketamine for chronic pain [38], a route that has been questioned previously [39].…”
Section: Toxicitymentioning
confidence: 95%
“…It is said that ketamine HCl administered intrathecally not only antagonises the NMDA receptors, but it also creates a sensory and motor blockage by blocking the calcium channels (2,8,10,16,17). Some researchers (6,20) have also noted that the effect of ketamine HCl is created by interacting with the opioid receptors in the spinal cord. El Shobary et al (6) claimed that it was more effective than morphine within the first 6 h after the operation and therefore, the IT ketamine could be used for postoperative analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers (6,20) have also noted that the effect of ketamine HCl is created by interacting with the opioid receptors in the spinal cord. El Shobary et al (6) claimed that it was more effective than morphine within the first 6 h after the operation and therefore, the IT ketamine could be used for postoperative analgesia. This study demonstrated that administering ketamine intrathecally achieved dissociative anaesthesia in a short time (1 min) and that even though the dissociative anaesthesia ended 95 min later, the anaesthesia has continued in the back legs and inguinal region (for other 17 min) as shown by clinical observation and pinprick tests.…”
Section: Discussionmentioning
confidence: 99%
“…but morphine provided prolonged analgesia in elderly patients. [18] Sethi et al studied ketamine in patient controlled epidural analgesia after abdominal surgery and concluded that ketamine reduces postoperative morphine consumption and is an effective adjuvant to local anesthetics. [19] Krishna T et al in their study opined that combined uses of ketamine and midazolam with intrathevcal bupivacaine provided prolonged analgesia compared to either ketamin or midazolam.…”
Section: Discussionmentioning
confidence: 99%